2018
DOI: 10.1111/bph.14126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corilagin on alleviating cholestasis via farnesoid X receptor‐associated pathways in vitro and in vivo

Abstract: Corilagin exerts a protective effect in hepatocytes and can prevent the deleterious activities of intrahepatic cholestasis by stimulating FXR-associated pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 62 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…In vitro , we assessed the viability of RAW264.7 cells pretreated with emodin at different concentrations (3.75, 7.5, 15, 30, 60, 120, 240, and 480 μg/ml) after 24 h. Based on the CCK-8 assay, the 75% viability of emodin concentration was calculated as 65.07 μg/ml. For convenience, we approximated high concentration as 60 μg/ml, middle concentration as 30 μg/ml, and low concentration as 15 μg/ml ( Yang et al, 2018 ). As shown in Figure 1A , the CCK-8 assay showed the viability of RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro , we assessed the viability of RAW264.7 cells pretreated with emodin at different concentrations (3.75, 7.5, 15, 30, 60, 120, 240, and 480 μg/ml) after 24 h. Based on the CCK-8 assay, the 75% viability of emodin concentration was calculated as 65.07 μg/ml. For convenience, we approximated high concentration as 60 μg/ml, middle concentration as 30 μg/ml, and low concentration as 15 μg/ml ( Yang et al, 2018 ). As shown in Figure 1A , the CCK-8 assay showed the viability of RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…After 24 h, the cells were harvested to detect the level of the TLR4 downstream signaling molecule TRAF-6 by western blotting to determine the optimal dosage of LPS. RAW264.7 cells were divided into a normal group, a model group, a DEX (0.5 μg/ml, diluted in PBS medium) group ( Yang et al, 2018 ) and emodin (15, 30, and 60 μg/ml, dissolved in DMSO and then diluted in PBS medium to a final DMSO concentration less than 0.1%) groups. After placing the cells in 6-well plates overnight and culturing to 80% density, LPS (1 μg/ml) was added to the wells for 2 h, and then DXM and emodin were added as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is an improvement on guidewire-induced injury method that was mentioned in published articles ( 28 , 29 ). According to our previous study ( 30 ), we designed a preliminary experiment to verify the concentrations and mortality curve ( Supplemental Figure 3 ). Then, we treated rats with high (40 mg/kg·day), medium (20 mg/kg·day), or low (10 mg/kg·day) concentrations of corilagin in corilagin groups, aspirin (20 mg/kg·day) in the aspirin group, or physiologic (0.9%) saline in the control group, sham-operation group, and model group, by means of intragastric administration for 1 month.…”
Section: Methodsmentioning
confidence: 99%
“…Corilagin, as one of the active ingredients of Erodium stephaniahum, can significantly improve serum liver function indexes of cholestasis rats, and regulate antioxidant and anti-inflammatory mechanisms (Jin et al, 2013). It can also activate FXR, SHP1, SHP2, UGT2B4, BSEP, MRP2, and SULT2A1 expression, down-regulate CYP7A1 and NTCP protein expression to improve cholestasis (Yang et al, 2018). Studies have shown that auraptene, the active ingredient in Citrus reticulata, reduces bile acid synthesis by activating the expression of FXR to reduce CYP7A1 and CYP8B1, and increases bile acid transporters (such as BSEP and MRP2) to increase bile acid transport (Gao et al, 2017).…”
Section: Main Bile Acid Receptor Drugs Fxr Agonistsmentioning
confidence: 99%